CREDIT QUALITY AFTER THE CRISIS: AN ONGOING CHALLENGE OF BANKING SECTOR IN ALBANIA - Celo, Robert; Kociu, Lorenc; Veizi, Zamira (European Scientific Journal, ESJ, 2015)
With increasingly development of banking system in Albania, credit quality and other specific factors, have always been a concern not only for bankers, but for all those who take part in the business world, because the default of one party can cause serious problems in the financial situation and in economic indicators of the other party. The development of the financial system has a significant impact on economic development. This impact is determined by the quality of lending, from the allocation of savings and other sources of lending to more successful projects. Recent years, Albanian banking sector is characterized by important developments that have a significant impact on the economy of the whole country. After 2007, is noticed a high growth of nonperforming loans in Albanian banking system, mainly as a result of the global financial crisis, but at the same time due to external and internal factors. The effect of the economic crisis is dominant external main factor in the growth of NPL (non- performing loans). Loan portfolio in Albanian banking system has been good until 2007. Levels of NPL have begun to grow from 2008 and continue. The main objective in this paper is to explain as credit quality in the Albanian banking system is deteriorated recent years.